Business Administration students taking english VII at Instituto Tecnológico de Costa Rica, Sede,San Carlos visited the Inniversity of Florida, Gainesville, United States. (Instituto Tecnológico de Costa Rica, 2019)
The academic field trip to the University of Florida (UF), located in Gainesville, Florida took place from February 21st to 27th, 2016. The main objective of this field trip was to achieve meaningful learning of social and academic interaction with Business Administration content and English linguistic knowledge.